1996
DOI: 10.1148/radiology.198.1.8539380
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of fat-suppressed three-dimensional spoiled gradient-echo FLASH MR imaging in the detection of patellofemoral articular cartilage abnormalities.

Abstract: T1-weighted FS 3D FLASH imaging is accurate for the detection and grading of articular cartilage abnormalities of the patellofemoral joint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
192
2
8

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 358 publications
(214 citation statements)
references
References 0 publications
8
192
2
8
Order By: Relevance
“…MR sequences used for semiquantitative scoring of cartilage lesions involve T 1 -weighted spoiled gradient recalled acquisition at steady state (SPGR ¼ spoiled gradient echo or FLASH ¼ fast low-angle shot) with fat suppression (38,(40)(41)(42)(43)(44)(45)(46)(47) the internal structure of the cartilage displays a more heterogeneous signal and 'internal' pathological changes may be more readily displayed. Also, cartilage surface lesions are well depicted with these sequences, because of the steep gradient of signal intensity between the cartilage and the synovial fluid, in particular when effusion is present [ Fig.…”
Section: Semiquantitative Scoring Of Articular Tissues In Oa Hardwarementioning
confidence: 99%
See 2 more Smart Citations
“…MR sequences used for semiquantitative scoring of cartilage lesions involve T 1 -weighted spoiled gradient recalled acquisition at steady state (SPGR ¼ spoiled gradient echo or FLASH ¼ fast low-angle shot) with fat suppression (38,(40)(41)(42)(43)(44)(45)(46)(47) the internal structure of the cartilage displays a more heterogeneous signal and 'internal' pathological changes may be more readily displayed. Also, cartilage surface lesions are well depicted with these sequences, because of the steep gradient of signal intensity between the cartilage and the synovial fluid, in particular when effusion is present [ Fig.…”
Section: Semiquantitative Scoring Of Articular Tissues In Oa Hardwarementioning
confidence: 99%
“…Satisfactory specificity and sensitivity for detecting chondral lesions has been demonstrated in cadaveric knees and in vivo with arthroscopic verification (40)(41)(42)(48)(49)(50)53). Bredella et al (51) reported a sensitivity of 93% and a specificity of 99% in detecting chondral lesions versus athroscopy when axial and coronal images were combined, and values of 94/99% when images in all three planes were combined.…”
Section: Technical Accuracy and Precision Of Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The modified Noyes and Stabler classification, as described by Recht et al, was used to grade macroscopically the talocrural joint cartilage surfaces. 300,326 Eleven specimens were graded 0 (intact cartilage). One specimen had a grade 3A lesion and was excluded from the study.…”
Section: Specimensmentioning
confidence: 99%
“…It is sensitive to metallic artifacts (6). These are the sequences that need to be adjusted using software before interpretation.…”
Section: Discussionmentioning
confidence: 99%